Marketing values of antidepressant drug and similar plants in mersin province - Uğur, Ali; Everest, Ayşe (Journal of Dependence, 2017)
This study contain the marketing values in herbalmarkets and pharmacies of the cope of with depression was one of the important problem. This work done between August to October in 2016. The informants were collected by interview with herbalists and pharmacies and Mersin city health administrative..
Keywords: smartphone addiction; university; student